Weaning Time Affects the Archaeal Community Structure and Functional Potential in Pigs - Deng, Feilong; Peng, Yunjuan; Zhang, Zhihao; Howe, Samantha; Wu, Zhuosui; Dou, Jieying; Li, Yuling; Wei, Xiaoyuan; Wang, Xiaofan; Liang, Yong; Zhao, Jiangchao; Li, Ying (Frontiers in Microbiology, 2022)
Archaea are considered a “keystone” of the gut microbiome and are linked with the host’s energy harvest and health. Although a few studies have investigated the gut archaea in pigs, especially piglets, little is known about the effects of weaning on archaeal structure and function. In this study, we explored the effects of weaning on the longitudinal changes of archaeal composition, diversity, and functional potential in pigs overtime by re-analyzing a recently published metagenomic dataset (Holman et al., 2021) that included 176 fecal samples collected from commercial pigs on days 7, 14, 21, 28, 35, 70, and 140 after birth. Overall, the richness and diversity of archaeal species showed an increasing trend, and weaning significantly affected the richness of archaeal species. Methanobrevibacter A smithii significantly decreased and was replaced by Methanobrevibacter A sp900769095 within two weeks after weaning. For the functional potential, the richness of KEGG KOs increased over time. LEfSe analysis identified 18 KOs, including for example, ko04623 (cytosolic DNA-sensing pathway), ko00500 (starch and sucrose metabolism) and so on, significantly enriched in the weaning pigs, suggesting the involvement of archaea in the piglets’ adaptation to the new diet after weaning. Correlation analysis based on Random Forest regression and Pearson correlation showed that archaeal species richness was significantly associated with pig body weight on both days 70 and 140. Methanobrevibacter A sp900769095 (R=0.405, P=0.040) and Methanobrevibacter A smithii (R=0.535, P=0.004) were positively linked with pigs’ body weight on days 70 and 140, respectively. Our results revealed the dynamic changes of archaeal diversity and functions and demonstrated the effects of weaning on the gut archaea of pigs, suggesting archaea might play essential roles in swine nutrition, metabolism, and growth performance, especially during the critical weaning process.